PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL PADA PROVINSI JAWA TENGAH (Studi Kasus Pada Kabupaten/Kota Provinsi Jawa Tengah Periode 2007-2011) (STIE YPPI Rembang, 2015)
AbstractThe purpose of this research is to find out whether Economic Growth, Local Own Revenue, General Alocation Fund, Special Alocation Fund influence the Capital Expenditure at Provinsi Central Java. The analyze method that is used in this research is quantitative method with multiple linier regression with bring about classical assumption test. The variable used in this research are Economic Growth, Local Own Revenue, General Alocation Fund, special Alocation Fund as independent variable and the Capital Expenditure as dependent variable. Amount of this research population counted 29 Sub-Province and 6 town from year 2007 up to year 2011. The result proof that Economic Growth, Local Own Revenue, General Alocation Fund, Special Alocation Fund influence significanly and simultaneously the Capital Expenditure of regencies and cities in Central Java. Adjusted R2 expressed that 79,1% influence given by Independent variables. The rest 20,9% influence given by other variables is not mentioned in this research model, Partially Regional Own Revenue, and General Alocation Fund, variable influence Capital Expenditure. Economic Growth with PDRB and Special Alocation Fund with actual price have no significant influence to the Capital Expenditure.Â Keywords: Economic Growth, Regional Own Revenue, General Alocation Fund, Special Alocation Fund and Capital Expenditure.